(untitled) (Plant Bulletin, 2024)
The experiment carried out during 2021–22, aimed to compare the performance of different soybean varieties under the environmental conditions of Tandojam. The treatments included T1 = Ajmeri, T2 = Rawal, and T3 = NARC-1. The soybean Rawal ranked first with a 64.00 cm plant height, 4.60 m2 leaf area index, 0.29 g seed weight, 7610 kg ha-1 biological yield, 3666 kg ha-1 seed yield, and 48.17% harvest index. Ajmeri variety significantly and ranked 2nd with 58.49 cm plant height, 4.21 m2 leaf area index, 0.23 g seed weight, 7129 kg ha-1 biological yield, 3268 kg ha-1 seed yield, and 46.18% harvest index. The soybean variety NARC-1 ranked least in performance with 56.31 cm plant height, 3.79 m2 leaf area index, 0.17 g seed weight, 7000 kg ha-1 biological yield, 3233 kg ha-1 seed yield, and a 45.84% harvest index. From the presented study, it was concluded that of the soybean varieties evaluated in this study, the variety Rawal (48.17 kg ha-1) showed better overall performance and maximum yield as compared to Ajmeri (46.18 kg ha-1) and NARC-1 (45.84 kg ha-1). However, the newly developed variety Rawal excelled in yield traits and demonstrated promising performance, indicating its potential as a future variety.